The influence of education level and job type on work-related travel patterns within rural metro-adjacent regions: The case of Castilla-La Mancha, Spain - Mohino, Inmaculada; Ureña, José M.; Solís, Eloy (Journal of Transport and Land Use, 2019)
Contemporary functional linkages and their relationships with the underlying settlement structure have been widely explored within polycentric urban configurations, but little attention has been paid to their adjacent rural regions. This paper examines the spatial patterns of commuting versus business travel in rural metro-adjacent regions to explain their reconfigured urban structures. These travel patterns are compared by considering workers’ education levels and occupations to investigate how rural metro-adjacent regions offer different opportunities for highly and non-highly skilled workers. Based on two surveys conducted by the authors in 2012, this work focuses on Castilla-La Mancha (CLM, Spain), a rural region under the influence of Madrid. The empirical results demonstrate the effectiveness of considering different functional linkages when explaining the underlying urban network. In particular, the results reinforce the idea of consolidating the polycentric spatial organization of urban centers in CLM, although this concentration is greater for commuting travel purposes and for highly skilled professionals. Conversely, the openness of CLM to other Spanish regions (including the adjacent metropolitan region) is greater for business travel than for commuting. The results also illustrate that the level of engagement, both in commuting and in business travel, increases with education. Finally, the results show that business travel occurs over longer distances than commuting does for all workers residing in rural metro-adjacent regions, regardless of education.